Diseño de un dispositivo de accionamiento y control para sistemas de inyección diesel EUI-UPS (2017)
In this project of degree is presented the design of a complete device for the tasks of setting up the diesel injection units, satisfying the basic requirements by the Omega Diesel Laboratory Ltda., Company interested in the same. Design alternatives were evaluated in the system of subjection of the injector units to the device, making the assembly and disassembly task efficient for the technician-operator. After identifying the alternatives an evaluation was made to select the one that fulfilled the requirements by the company. Based on the detailed design of the device, the specific design was performed for each of the elements involved in the drive process, the permissible stresses of each element were evaluated by materials resistance calculations and some of them by analysis of finite elements. The operating manual of the device was elaborated, recommendations for use and important aspects to be taken into account. In addition, plans were drawn up and finally a financial evaluation of the project was carried out to visualize the viability of the project.